Open and closed metal hydride system for high thermal power applications: Preheating vehicle components. (20th April 2017) - Dieterich, Mila; Bürger, Inga; Linder, Marc
Abstract: Many vehicle components operate at temperatures above ambient conditions. At cold start, most of the pollutants are produced and lifespan is reduced. Thermochemical energy storage with high power density could prevent these disadvantages. In order to investigate achievable power densities of a thermochemical energy storage at technically relevant boundary conditions, a laboratory scale device using metal hydrides (LaNi4.85 Al0.15 and C5 ® ) is designed and preheating operation modes (open and closed) are analyzed. The impact of the ambient temperature (from −20 to +20 °C), a s well as other influencing factors on the thermal power output such as heat transfer flow rate, regeneration temperature and pressure conditions are investigated. The experiments proved the suitability of the reactor design and material selection for the considered application boundary conditions. For the coupled reaction (closed system), the ambient temperature has the greatest influence on the thermal power with decreasing values for lower temperatures. Here, values between 0.6 kW/kgMH at ambient temperature of −20 °C and 1.6 kW/kgMH at 20 °C, at otherwise same conditions, were reached. If hydrogen can be supplied from a pressure tank (open system), the supply pressure in relation to equilibrium pressure at the considered ambient temperature has to be large enough for high thermal power. At −20 °C, 1.4 kW/kgMH at a supply pressure of 1.5 bar and 5.4 kW/kgMH at a hydrogen pressure of 10 bar were reached. Highlights: High thermal power of metal hydrides preheating vehicle components at −20 °C shown. Ambient temperature had the biggest influence on the thermal power. The coupled reaction reached 0.6 kW/kgMH at −20 °C and 1.6 kW/kgMH at 20 °C. At −20 °C and a constant H2 -pressure of 10 bar, 5.4 kW/kgMH were reached.